Composite binder, preparation process of artificial graphite, artificial graphite and application
Patent Information
- Application Number
- CN202510860005.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-06-25
AI Technical Summary
但入炉块体和出炉块体对于粘接剂的要求于某种程度上是相互矛盾的:如果入炉块体的结构强度过高,出炉石墨化块通常需要提高解聚强度才能获得高粒径一致性的粉体,而高解聚强度会导致颗粒形貌恶化,比表增大,首效降低
[0072]为更好地说明本发明的目的、技术方案和有益效果,下面将结合具体实施例对本发明作进一步说明。需说明的是,下述实施所述方法是对本发明做的进一步解释说明,不应当作为对本发明的限制。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy technology, particularly to the field of material synthesis technology for secondary batteries, and even more particularly to the preparation process of composite binders and artificial graphite, artificial graphite and its applications. Background Technology
[0002] Artificial graphite is currently the most widely used anode material. It is generally made from needle coke or petroleum coke as raw materials and is a powder material prepared through processes such as crushing, shaping, granulation, graphitization, and coating carbonization.
[0003] Graphitization is one of the core processes in the preparation of artificial graphite. Currently, the graphitization process mainly uses intermittent graphitization furnaces. This involves electrically heating resistance materials, graphite plates, and crucibles, followed by heat treatment of the coke powder to achieve structural evolution, ultimately forming graphite. Because the graphitization process requires auxiliary materials such as insulating materials, resistance materials, graphite crucibles, and graphite boxes, heating these auxiliary materials consumes a significant amount of energy, resulting in a low thermal energy utilization rate (~50%) for intermittent graphitization furnaces. Furthermore, due to differences in temperature field distribution, the degree of graphitization varies at different locations (furnace head / tail, upper / lower layers), weakening the consistency of graphitized product indicators.
[0004] Compared to intermittent graphitization furnaces, continuous graphitization furnaces offer higher thermal efficiency (no auxiliary materials required), shorter production cycles, ultra-low manufacturing costs, and less flue gas emission. The residence time of materials in the high-temperature zone can be precisely controlled by adjusting the furnace feeding and discharging processes, significantly improving the consistency of graphitized products. However, since the materials are typically micron-sized powders, directly feeding them into a continuous graphitization furnace can easily cause material leakage, furnace spraying, and blockage at the discharge port. Therefore, a binder is needed to bond the powder into granules. On one hand, the gaps between the granules allow waste gas generated during heat treatment to escape through these gaps, preventing furnace spraying and ensuring smoother material discharge. On the other hand, the material throughput per furnace is also increased.
[0005] In continuous graphitization processes, the use of binders ensures the structural integrity of the carbonized blocks before and during the graphitization furnace, preventing them from disintegrating. After graphitization, the graphite blocks either disperse on their own or through a micro-depolymerization process, resulting in graphitized products with high particle size uniformity, moderate specific surface area, and regular morphology. However, the requirements for binders in the incoming and outgoing blocks are somewhat contradictory: if the structural strength of the incoming blocks is too high, the outgoing graphitized blocks usually require increased depolymerization strength to obtain powder with high particle size uniformity. However, high depolymerization strength leads to deterioration of particle morphology, increased specific surface area, and reduced initial efficiency. Conversely, if the outgoing graphitized blocks exhibit excessive depolymerization, the structural strength of the incoming blocks will be greatly weakened, leading to particle disintegration in the early stages of graphitization, causing material blockage or even furnace blowout risks.
[0006] Therefore, how to rationally design the binder components and structure to meet the different performance requirements of the furnace-entry and furnace-exit blocks in order to obtain graphitized products with better performance is of great significance for improving the performance of graphitized products. Summary of the Invention
[0007] To address the aforementioned problems, this invention provides a composite binder, a preparation process for artificial graphite, artificial graphite, and its applications. This composite binder combines binders with specific parameters and content, supplemented with a crosslinking agent. This avoids the fragmentation of the blocks during furnace loading caused by falling, tumbling, squeezing, and collisions, ensuring the integrity of the block structure. It also guarantees the easy depolymerization of the graphitized blocks, preventing strong depolymerization from damaging the graphite surface morphology. Therefore, it improves the problem of low initial coulombic efficiency in artificial graphite, resulting in a graphite anode material with satisfactory specifications and performance.
[0008] To achieve the above objectives, the first aspect of the present invention provides a composite binder for producing artificial graphite from a graphite precursor through continuous graphitization. The composite binder comprises component A, component B, and component C. Component A comprises a soft carbon binder, component B comprises a hard carbon binder, and component C comprises a crosslinking agent. The soft carbon binder satisfies either equation one or equation two, the residual carbon content of component A is 'a', the residual carbon content of component B is 'b', a+b≤2.90%, a / (a+b)≥60%, and the mass ratio of component C to component A is ≤20%. SP T is the temperature at which the soft carbon binder transitions from a solid to a molten liquid state. IFT The temperature at which the contact angle between the soft carbon binder and the base coke raw material is 90° is defined as the temperature at which the contact angle is 90°. The residual carbon content is the product of the coking value and its mass percentage in the graphite precursor.
[0009] (T IFT -T SP ) / T SP ≤0.30T SP ≤150℃ Relationship 1
[0010] (T IFT -T SP ) / T SP ≤0.12T SP >150℃ Relationship 2
[0011] The composite binder of this invention includes a soft carbon binder, a hard carbon binder, and a crosslinking agent with specific parameters and contents. Component A is selected that satisfies either Equation 1 or Equation 2, and a soft carbon binder with a certain coking value is selected and its content is controlled (i.e., it has a certain residual carbon content) to ensure high affinity. The soft carbon binder has good graphitization ability, better affinity with graphite precursors, and can also provide structural support at high temperatures. It also has a certain modifying effect on the graphite surface. However, in the medium-low temperature range of 200–400°C, internal molecular solubilization occurs, resulting in decreased viscosity and significantly weakened structural support. Adding a hard carbon binder can compensate for this defect. Compared to soft carbon binders, hard carbon binders are more difficult to graphitize and have a more significant effect on particle bonding. They can provide structural support at medium and low temperatures of 200–400℃. However, the structural support is weakened after high-temperature heat treatment, and excessive hard carbon binders will reduce the initial coulombic efficiency of the material. Therefore, controlling a / (a+b)≥60% to keep the content of component B low can both compensate for the problems of soft carbon binders in the medium and low temperature range and avoid the negative effects of high temperature and high content. Furthermore, by adding a small amount of crosslinking agent to the soft carbon binder and hard carbon binder, the crosslinking agent can induce crosslinking reactions in the soft carbon binder molecules, increase the system viscosity, enhance structural stability, shorten the low viscosity temperature window, accelerate curing and molding, and prevent structural collapse caused by the melting and softening of the soft carbon binder. Therefore, under the action of the crosslinking agent, by controlling a+b≤2.90%, the use of low residual carbon A and B components can meet the strength requirements of continuous graphitization. The low residual carbon content can also improve the depolymerization properties of the graphitized product, thereby meeting the different requirements of the binder for the furnace block and the unfired block in continuous graphitization. In short, this invention, by selecting a composite binder including soft carbon binder, hard carbon binder, and crosslinking agent with certain parameters and contents, can ensure a stable structure in both the medium and low temperature ranges and the high temperature range, while also exhibiting better depolymerization properties. This avoids the problem of poor performance of the artificial graphite caused by the different requirements of the binder for the furnace block and the unfired block in continuous graphitization.
[0012] As a technical solution of the present invention, the soft carbon binder is selected from at least one of oil-based asphalt, coal-based asphalt, impregnated asphalt, modified asphalt, and high softening point asphalt.
[0013] As one technical solution of the present invention, the hard carbon binder is selected from at least one of phenolic resin, epoxy resin, coumarone resin, biomass oil, cassava flour and water-soluble starch.
[0014] As one technical solution of the present invention, the crosslinking agent is selected from at least one of terephthalic acid, benzaldehyde, p-methylbenzaldehyde, p-phenylenediamine, p-toluenesulfonic acid, sulfur, N-bromosuccinimide and N-iodosuccinimide.
[0015] As a technical solution of the present invention, component B further includes a polymer adhesive, wherein the polymer adhesive is selected from at least one of polyacrylic acid, styrene-butadiene-styrene block copolymer, ethylene-octene copolymer, ethylene-ethyl acrylate copolymer, styrene-ethylene / butene-styrene triblock copolymer, ethylene-octene copolymer, chloroprene rubber, ethylene-ethyl acrylate copolymer, sodium carboxymethyl cellulose, polyvinylidene fluoride, and polyethylene terephthalate.
[0016] As a technical solution of the present invention, the T SP The results were obtained using a Mettler DP70 tester.
[0017] As a technical solution of the present invention, the T IFT The results were obtained using a Dataphysics OCA20 measuring instrument.
[0018] A second aspect of this invention provides a process for preparing artificial graphite, comprising the steps of:
[0019] (1) Select a graphitization binder
[0020] The adhesive used is the aforementioned composite adhesive;
[0021] (2) Mixing
[0022] The graphite precursor, component A, component B, component C, and solvent are mixed to obtain a mixture;
[0023] (3) Molding, drying and carbonization
[0024] The mixture is sequentially pressed into balls, dried, and carbonized to obtain a carbonized body, the pulverization resistance factor of which is η. 碳化 50kPa≤η 碳化 ≤90kPa;
[0025] (4) Continuous graphitization
[0026] The carbide is graphitized to obtain a graphitized body, and the graphitized body has a powdering resistance factor of η. 石墨化 20kPa≤η 石墨化 ≤36kPa;
[0027] (5) Post-processing
[0028] The graphitized body is then post-processed.
[0029] The preparation method of this invention uses a composite binder with certain parameters and contents of soft carbon binder, hard carbon binder, and crosslinking agent for carbonization and graphitization. Before graphitization, a powdering resistance factor η can be obtained. 碳化 It is a carbide with a strength of 50-90 and a high η. 碳化 This ensures the structural integrity of the blocks before and during the initial stage of graphitization, as well as the safety of the graphitization furnace. Due to the low residual carbon content design of the composite binder, the graphitization treatment yields a high powdering resistance factor η. 石墨化 Graphitized materials with values of 20–36 and low η 石墨化 This process can give graphitized materials better depolymerization properties. Therefore, graphite materials with high particle size uniformity and regular morphology can be obtained through micro-depolymerization process, thereby improving the problem of low initial coulombic efficiency of graphitized products and obtaining graphite materials with the required indicators and performance.
[0030] As a technical solution of the present invention, the graphite precursor is selected from at least one of needle coke, calcined needle coke, petroleum coke, calcined petroleum coke and isotropic coke.
[0031] As one technical solution of the present invention, the particle size Dv50 of the graphite precursor is 6-25 μm.
[0032] As one technical solution of the present invention, the solvent is selected from at least one of water, ethanol, isopropanol, toluene, tetrahydrofuran, N-methyl-2-pyrrolidone, n-heptane, n-hexane, cyclohexane, acetone and N,N-dimethylformamide.
[0033] As one technical solution of the present invention, the solvent accounts for 7-25% of the mass of the mixture.
[0034] As one technical solution of the present invention, the carbide is a sphere, an ellipsoid, or a cylinder.
[0035] As one technical solution of the present invention, the carbide is a cylinder with a diameter of 8-40 mm and a height h of 8-30 mm.
[0036] As a technical solution of the present invention, the powdering resistance factor after drying is η. 烘干 120kPa≤η 烘干 ≤145kPa.
[0037] As one technical solution of the present invention, the equipment used for mixing is selected from glass reactors, stainless steel reactors, double planetary mixers, kneaders, VC mixers, fusion machines, or three-dimensional mixers.
[0038] As a technical solution of the present invention, the pressing method is selected from molding, roller extrusion, rotary rolling or extrusion molding.
[0039] As one technical solution of the present invention, the drying temperature is 70-350°C and the drying time is 2-15 hours.
[0040] As one technical solution of the present invention, the carbonization temperature is 900-1250°C and the time is 3-15 hours.
[0041] As a technical solution of the present invention, the post-processing includes depolymerization, which is performed using a depolymerization machine with a main frequency of 10-25Hz.
[0042] As one technical solution of the present invention, the graphitization process is carried out in a continuous graphitization furnace.
[0043] As one technical solution of the present invention, the temperature of the continuous graphitization furnace is 2600-3200℃ and the time is 2-10h.
[0044] The third aspect of the present invention provides artificial graphite prepared by the aforementioned artificial graphite preparation process.
[0045] As one technical solution of the present invention, the particle size Dv50 of the artificial graphite is 7-25 μm.
[0046] As one technical solution of the present invention, the specific surface area of the artificial graphite is 0.5 to 2.5 m². 2 / g.
[0047] As one technical solution of the present invention, the specific capacity of the artificial graphite is 320-355 mAh / g.
[0048] As a technical solution of the present invention, the initial coulombic efficiency of the artificial graphite is ≥93.2%.
[0049] The fourth aspect of the present invention provides artificial graphite prepared by the aforementioned artificial graphite preparation process or the application of the aforementioned artificial graphite in batteries.
[0050] The fifth aspect of the present invention provides a secondary battery, comprising a positive electrode material, a negative electrode material, and an electrolyte, wherein the negative electrode material comprises artificial graphite prepared by the aforementioned artificial graphite preparation process or the aforementioned artificial graphite. Detailed Implementation
[0051] The artificial graphite of the present invention can be used as a negative electrode material for batteries. It can be used alone or in combination with other negative electrode active materials (such as natural graphite, silicon materials, silicon-carbon materials, silicon-oxygen materials, soft carbon and / or hard carbon, etc.).
[0052] Artificial graphite can be used in secondary batteries, which include positive electrode materials, negative electrode materials, and electrolytes.
[0053] The cathode material includes at least one of lithium cobalt oxide cathode materials, lithium iron phosphate cathode materials, lithium nickel cobalt manganese oxide cathode materials, and lithium nickel cobalt aluminum oxide cathode materials. Among them, the lithium cobalt oxide cathode material can be lithium cobalt oxide, doped or coated lithium cobalt oxide. The lithium iron phosphate cathode material can be lithium iron phosphate, doped or coated lithium iron phosphate. The lithium nickel cobalt manganese oxide cathode material can be lithium nickel cobalt manganese oxide, doped or coated lithium nickel cobalt manganese oxide. The lithium nickel cobalt aluminum oxide cathode material can be lithium nickel cobalt aluminum oxide, doped or coated lithium nickel cobalt aluminum oxide.
[0054] The electrolyte comprises an electrolyte salt, a non-aqueous organic solvent, and additives. The electrolyte salt may be, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium dioxalate borate (C4BLiO8), lithium difluorooxalate borate (C2BF2LiO4), lithium difluorophosphate (LiPO2F2), and lithium difluorobis(oxalate) phosphate (LiDFBP). The non-aqueous organic solvent is selected from carbonates and / or carboxylic acid esters. Furthermore, the non-aqueous organic solvent is selected from at least one of ethylene carbonate (PC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl methyl carbonate (EMC), γ-butyrolactone, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, ethyl propionate, propyl propionate, and butyl propionate. The additive may be vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), 1,3-propenesulfonate lactone (PST), or methyl methylene disulfonate (MMDS), etc.
[0055] The particle size Dv50 of the artificial graphite of this invention is 7–25 μm. As an example, Dv50 can be, but is not limited to, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 20 μm, 21 μm, 23 μm, and 25 μm. The specific surface area of the artificial graphite is 0.5–2.5 m². 2 / g, as an example, the specific surface area can be, but is not limited to, 0.5m². 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.3m 2 / g, 1.5m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.2m 2 / g, 2.5m 2 / g. The specific capacity of artificial graphite is 320–355 mAh / g. For example, the specific capacity may be, but is not limited to, 320 mAh / g, 325 mAh / g, 330 mAh / g, 335 mAh / g, 340 mAh / g, 345 mAh / g, 350 mAh / g, and 355 mAh / g. The initial coulombic efficiency of artificial graphite is ≥92.5%. For example, the initial coulombic efficiency may be, but is not limited to, 92.5%, 93.0%, 93.5%, 94.0%, 94.5%, 95.0%, 95.5%, and 96.0%.
[0056] The artificial graphite of the present invention can be prepared by the following steps: (1) selecting a graphitizing binder; (2) mixing; (3) molding, drying and carbonizing; (4) continuous graphitization; and (5) post-treatment.
[0057] Step (1) Select a graphitization binder, which may be a composite binder. The composite binder may include component A, component B and component C.
[0058] Component A includes a soft carbon binder, which is selected from at least one of oil-based asphalt, coal-based asphalt, impregnated asphalt, modified asphalt, and high softening-point asphalt. The soft carbon binder is not only selected from these substances but also satisfies either Relationship 1 or Relationship 2. T SP The temperature at which the soft carbon binder transitions from a solid to a molten liquid state was determined using a Mettler DP70 tester. IFT The temperature at which the contact angle between the soft carbon binder and the base coke raw material is 90° is measured using a Dataphysics OCA20 measuring instrument.
[0059] (T IFT -T SP ) / T SP ≤0.30T SP ≤150℃ Relationship 1
[0060] (T IFT -T SP ) / T SP ≤0.12T SP >150℃ Relationship 2
[0061] Component B includes a hard carbon binder selected from at least one of phenolic resin, epoxy resin, coumarone resin, biomass oil, cassava flour, and water-soluble starch. Further, Component B also includes a polymer binder selected from at least one of polyacrylic acid, styrene-butadiene-styrene block copolymer, ethylene-octene copolymer, ethylene-ethyl acrylate copolymer, styrene-ethylene / butene-styrene triblock copolymer, ethylene-octene copolymer, chloroprene rubber, ethylene-ethyl acrylate copolymer, sodium carboxymethyl cellulose, polyvinylidene fluoride, and polyethylene terephthalate.
[0062] To ensure a stable structure during the graphitization process across both low and high temperature ranges, soft carbon binders, hard carbon binders, and polymer binders with specific coking values can be selected. Simultaneously, their mass percentage in the graphite precursor should be controlled, i.e., the residual carbon content (the product of the coking value and the mass percentage in the graphite precursor) should be controlled. The residual carbon content of component A is denoted as 'a', and the residual carbon content of component B is denoted as 'b', where a+b≤2.90% and a / (a+b)≥60%. The ratio of hard carbon binder to polymer binder in component B can be determined based on actual conditions, only requiring that a+b≤2.90% and a / (a+b)≥60%. Furthermore, a+b can be, but is not limited to, 2.90%, 2.85%, 2.80%, 2.75%, 2.70%, 2.65%, 2.60%, 2.55%, 2.50%, 2.45%, 2.40%, 2.35%, 2.30%, 2.25%, 2.20%, 2.15%, 2.10%, 2.05%, and 2.00%. a / (a+b) can be, but is not limited to, 60%, 63%, 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85%, 88%, and 90%.
[0063] Component C includes a crosslinking agent selected from at least one of terephthalic acid, benzaldehyde, p-methylbenzaldehyde, p-phenylenediamine, p-toluenesulfonic acid, sulfur, N-bromosuccinimide, and N-iodosuccinimide. The mass percentage of component C in component A is ≤20%. For example, the percentage of component C may be, but is not limited to, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, or 10%.
[0064] Step (2) mixing involves mixing the graphite precursor, component A, component B, component C, and solvent to obtain a mixture. During operation, components A, B, and C can be mixed separately. For example, the graphite precursor, component A, and component C can be mixed to obtain a preliminary mixture, and then the preliminary mixture, component B, and solvent can be mixed to obtain a final mixture. Alternatively, the graphite precursor and component A can be mixed first to obtain a preliminary mixture, and then the preliminary mixture, component B, component C, and solvent can be mixed to obtain a final mixture.
[0065] The graphite precursor is selected from at least one of needle coke, calcined needle coke, petroleum coke, calcined petroleum coke, and isotropic coke. The particle size Dv50 of the graphite precursor is 6–25 μm, and as an example, Dv50 may be, but is not limited to, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, and 25 μm. The solvent is selected from at least one of water, ethanol, isopropanol, toluene, tetrahydrofuran, N-methyl-2-pyrrolidone, n-heptane, n-hexane, cyclohexane, acetone, and N,N-dimethylformamide. The solvent accounts for 7–25% of the mass of the mixture, and as an example, the solvent percentage may be, but is not limited to, 7%, 9%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, and 25%. The equipment used for mixing can be selected from glass reactors, stainless steel reactors, double planetary mixers, kneaders, VC mixers, fusion machines, or three-dimensional mixers;
[0066] Step (3) Molding, drying and carbonization includes pressing the mixture into balls, drying and carbonizing them in sequence to obtain a carbonized body. The pulverization resistance factor of the carbonized body is η. 碳化 50kPa≤η 碳化 ≤90kPa, η 碳化 The pressures can be, but are not limited to, 50 kPa, 55 kPa, 60 kPa, 65 kPa, 70 kPa, 75 kPa, 80 kPa, 85 kPa, and 90 kPa. The pulverization resistance factor after drying is η. 烘干 120kPa≤η 烘干 ≤145kPa, η 烘干The pressure can be, but is not limited to, 120 kPa, 125 kPa, 130 kPa, 135 kPa, 140 kPa, or 145 kPa. The pressing method is selected from molding, roller extrusion, rotary rolling, or extrusion molding. The drying temperature is 70–350°C; for example, the temperature can be, but is not limited to, 70°C, 100°C, 150°C, 200°C, 250°C, 300°C, or 350°C. The drying time is 2–15 hours; for example, the time can be, but is not limited to, 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 14 hours, or 15 hours. The carbonization temperature is 900–1250°C; for example, the temperature can be, but is not limited to, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, or 1250°C. The time is 3 to 15 hours. For example, the time can be, but is not limited to, 3 hours, 5 hours, 7 hours, 9 hours, 10 hours, 11 hours, 13 hours, and 15 hours. The carbide is spherical, ellipsoidal, or cylindrical. If the carbide is cylindrical, the diameter is 8 to 40 mm and the height h is 8 to 30 mm.
[0067] Step (4) Continuous graphitization includes graphitizing the carbide to obtain a graphitized body, wherein the graphitized body has a powdering resistance factor of η. 石墨化 20kPa≤η 石墨化 ≤36kPa. η 石墨化 The pressures can be, but are not limited to, 20 kPa, 22 kPa, 24 kPa, 26 kPa, 28 kPa, 30 kPa, 32 kPa, 34 kPa, and 36 kPa. The graphitization process is carried out in a continuous graphitization furnace with a temperature of 2600–3200℃. For example, the temperatures can be, but are not limited to, 2600℃, 2650℃, 2700℃, 2750℃, 2800℃, 2850℃, 2900℃, 2950℃, 3000℃, 3050℃, 3100℃, 3150℃, and 3200℃. The time is 2–10 hours. For example, the time can be, but is not limited to, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours.
[0068] Step (5) post-processing includes post-processing the graphitized body, which includes depolymerization. Depolymerization is performed using a depolymerization machine with a main frequency of 10-25Hz. Since the graphitized body has good depolymerization properties, depolymerization can be performed at a low frequency.
[0069] Wherein, if the carbide is a sphere or an ellipsoid, the powdering resistance factor η = P cs *(D1-D2) / D1, P cs =a*F / (π*D2) 2D1 is the diameter of the sphere, μm; D2 is the diameter of the sphere when it bears the maximum pressure, μm; F is the maximum pressure the sphere bears, mN; and a is the collapse coefficient.
[0070] The testing process for the chalking resistance factor η can be as follows: Compress the mixture into spheres with a diameter of approximately 20 mm, and then prepare spherical samples. Measure the diameter D1 (μm) of the spherical sample using calipers. Preheat the universal testing machine and clean the sample stage surface, ensuring the pressure sensor reading is zero. Then place the spherical sample on the sample stage and gradually apply static pressure, recording the stress-strain curve to obtain the maximum pressure F (mN) that the spherical sample can withstand and the corresponding sphere size D2 (μm). Based on formula P... cs =a*F / (π*D2) 2 The compressive strength P of the sphere is obtained. cs (kPa), where a is the collapse coefficient, which is typically 2.48 × 10⁻⁶. 6 According to P cs Further calculations yielded the chalking resistance factor η = P cs *(D1-D2) / D1. Where, if the powdering resistance factor is η 烘干 The mixture is then pressed into spheres and then dried and hardened to obtain sphere samples. If the powdering resistance factor is η... 碳化 The mixture is then pressed into spheres, followed by drying, hardening, and carbonization to create sphere samples. If the powdering resistance factor is η... 石墨化 The mixture is then pressed into spheres, followed by drying, hardening, carbonization, and graphitization to obtain spherical samples. The pressing, drying, carbonization, and graphitization processes for testing the powdering resistance factor η can refer to those for artificial graphite, but the sample shape must remain essentially unchanged during the test.
[0071] If the carbide is cylindrical, the powdering resistance factor η = P cs *(H1-H2) / H1, P cs =a*F / (π*D) 2 D is the diameter of the cylinder (μm), H1 is the height of the cylinder (μm), H2 is the height of the cylinder when it withstands the maximum pressure (μm), F is the maximum pressure the cylinder can withstand (mN), and a is the collapsibility coefficient. The test procedure for the powdering resistance factor η can be referenced for a sphere, but when applying static pressure, pressure is applied to the height direction of the cylinder.
[0072] To better illustrate the purpose, technical solution, and beneficial effects of this invention, the invention will be further described below with reference to specific embodiments. It should be noted that the methods described below are further explanations of this invention and should not be construed as limiting it.
[0073] Example 1
[0074] This embodiment describes a process for preparing artificial graphite, which includes the following steps.
[0075] (1) Select a graphitization binder
[0076] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6% (T IFT -T SP ) / T SP =0.04. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0077] (2) Mixing
[0078] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%), oil-based asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of oil-based asphalt added was 3.04 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.75% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.304 wt.% and 0.051 wt.% (compared to calcined petroleum coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 2.65 wt.% (compared to calcined petroleum coke), the amount of PAA solution added is 0.56 wt.% (compared to calcined petroleum coke), therefore the residual carbon content of component B is 1.02%, and water accounts for 8.7% of the total mass of the mixture.
[0079] (3) Molding, drying and carbonization
[0080] The mixture was extruded to form spheres with a diameter of 19.2 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 180°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was measured. 烘干 The Pa is 132.1 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The pulverization resistance factor η of the carbide is... 碳化 The pressure is 82.6 kPa and the diameter is 18.7 mm.
[0081] (4) Continuous graphitization
[0082] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified].石墨化 The value is 31.3 kPa.
[0083] (5) Post-processing
[0084] The graphitized material was depolymerized in a depolymerizer with a main frequency of 19 Hz and D was controlled. V 50 is 11.0±1.5μm, thus obtaining artificial graphite.
[0085] Example 2
[0086] (1) Select a graphitization binder
[0087] The adhesive consists of components A, B, and C. Component A is T. SP Modified asphalt at temperatures below 150℃ has a coking value of 60.7%. IFT -T SP ) / T SP =0.24. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA aqueous solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0088] (2) Mixing
[0089] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%), modified asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of modified asphalt added was 2.88 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.75% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.288 wt.% and 0.048 wt.% (compared to calcined petroleum coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 2.65 wt.% (compared to calcined petroleum coke), the amount of PAA solution added is 0.56 wt.% (compared to calcined petroleum coke), therefore the residual carbon content of component B is 1.02%, and water accounts for 9.3% of the total mass of the mixture.
[0090] (3) Molding, drying and carbonization
[0091] The mixture was extruded to form spheres with a diameter of 20.8 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 170°C and holding for 4 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was determined. 烘干 The Pa is 128.3 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化The pressure is 78.3 kPa and the diameter is 20.3 mm.
[0092] (4) Continuous graphitization
[0093] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 28.2 kPa.
[0094] (5) Post-processing
[0095] The graphitized material was depolymerized in a depolymerizer with a main frequency of 17 Hz and D was controlled. V 50 is 11.0±1.5μm, thus obtaining artificial graphite.
[0096] Example 3
[0097] This embodiment describes a process for preparing artificial graphite, which includes the following steps.
[0098] (1) Select a graphitization binder
[0099] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6% (T IFT -T SP ) / T SP =0.04. Component B contains epoxy resin and sodium carboxymethyl cellulose powder. The coking value of the epoxy resin is 39.2%, and the coking value of the sodium carboxymethyl cellulose powder is 21.2%. Component C includes p-toluenesulfonic acid and p-methylbenzaldehyde.
[0100] (2) Mixing
[0101] Calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%) and oil-based asphalt were mixed with VC to obtain a primary mixture, wherein the amount of oil-based asphalt added was 2.86wt.% (compared to calcined petroleum coke), so the residual carbon content of component A was 1.65%. The obtained primary mixture, p-toluenebenzaldehyde, p-toluenesulfonic acid, epoxy resin, sodium carboxymethyl cellulose powder, ethanol and water were added to a kneading machine to obtain a mixture. The fusion machine operates at 150 rpm for 30 minutes. The amounts of p-methylbenzaldehyde and p-toluenesulfonic acid introduced are 0.372% and 0.149% (compared to calcined petroleum coke), respectively. The amount of epoxy resin added is 2.68 wt.% (compared to calcined petroleum coke), and the amount of sodium carboxymethyl cellulose powder added is 0.16 wt.% (compared to calcined petroleum coke). Therefore, the residual carbon content of component B is 1.08%, and ethanol and water (volume ratio of 1:9) account for 15.3% of the total mass of the mixture.
[0102] (3) Molding, drying and carbonization
[0103] The mixture was molded into cylinders with a diameter of 19.3 mm and a height of 17.8 mm. The pressed cylinders were then heat-treated at 75°C for 10 h, and then heated to 220°C and held for 4 h to obtain dried cylinders. The powdering resistance factor η of the dried cylinders was determined. 烘干 The Pa is 136.4 kPa, and then carbonized at 950 °C for 4 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化 The pressure is 65.5 kPa and the diameter is 17.2 mm.
[0104] (4) Continuous graphitization
[0105] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 25.3 kPa.
[0106] (5) Post-processing
[0107] The graphitized material was depolymerized in a depolymerizer with a host frequency of 16Hz and the DV50 was controlled to be 11.0±1.5μm to obtain artificial graphite.
[0108] Example 4
[0109] This embodiment describes a process for preparing artificial graphite, which includes the following steps.
[0110] (1) Select a graphitization binder
[0111] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 73.2% (T IFT -T SP ) / T SP =0.08. Component B contains thermosetting phenolic resin and PVDF powder. The coking value of the thermosetting phenolic resin is 37.7%, and the coking value of the PVDF powder is 34.6%. Component C is sulfur.
[0112] (2) Mixing
[0113] Calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%), oil-based asphalt, and sulfur were mixed with VC to obtain a primary mixture. The amount of oil-based asphalt added was 2.53 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.85% for component A and an sulfur content of 0.177 wt.% (compared to calcined petroleum coke). The primary mixture, thermosetting phenolic resin, PVDF powder, N-methylpyrrolidone, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 40 Hz, with a mixing time of 2.5 h. The amount of thermosetting phenolic resin added is 2.26 wt.% (compared to calcined petroleum coke), and the amount of PVDF powder added is 0.087 wt.% (compared to calcined petroleum coke). Therefore, the residual carbon content of component B is 0.88%, and N-methylpyrrolidone and water (volume ratio of 3:2) account for 18.6% of the total mass of the mixture.
[0114] (3) Molding, drying and carbonization
[0115] The mixture was extruded to form spheres with a diameter of 20.5 mm. The pressed spheres were then heat-treated at 80°C for 6 hours, followed by heating to 265°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was determined. 烘干 The Pa is 123.7 kPa, and then carbonized at 1150 °C for 5 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化 The pressure is 85.3 kPa and the diameter is 20.0 mm.
[0116] (4) Continuous graphitization
[0117] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 35.8 kPa.
[0118] (5) Post-processing
[0119] The graphitized material was depolymerized in a depolymerizer with a host frequency of 23Hz and the DV50 was controlled to be 11.0±1.5μm to obtain artificial graphite.
[0120] Example 5
[0121] This embodiment describes a process for preparing artificial graphite, which includes the following steps.
[0122] (1) Select a graphitization binder
[0123] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6% (T IFT -T SP) / T SP =0.04. Component B contains thermosetting phenolic resin and chloroprene rubber. The coking value of the thermosetting phenolic resin is 37.7%, and the solid content of the chloroprene rubber is 30%, with a coking value of 18.9%. Component C is N-bromosuccinimide.
[0124] (2) Mixing
[0125] Calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%) and oil-based asphalt were mixed with VC to obtain a primary mixture. The amount of oil-based asphalt added was 2.60 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.50% for component A. The primary mixture, N-bromosuccinimide, thermosetting phenolic resin, chloroprene rubber, and water were then added to a kneader and kneaded to obtain a final mixture. The kneader speed was 35 Hz, and the kneading time was 2 h. The amount of N-bromosuccinimide introduced was 0.26 wt.% (compared to calcined petroleum coke), the amount of thermosetting phenolic resin added was 2.39 wt.% (compared to calcined petroleum coke), and the amount of chloroprene rubber added was 1.41 wt.% (compared to calcined petroleum coke). Therefore, the carbon residue of component B was 0.98%, and water accounted for 20.6% of the total mass of the mixture.
[0126] (3) Molding, drying and carbonization
[0127] The mixture was extruded to form spheres with a diameter of 18.3 mm. The extruded spheres were then heat-treated at 95°C for 2 hours, followed by heating to 235°C and holding for 2 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was... 烘干 The Pa is 125.4 kPa, and then carbonized at 1150 °C for 5 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化 The pressure is 57.6 kPa and the diameter is 17.7 mm.
[0128] (4) Continuous graphitization
[0129] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 22.4 kPa.
[0130] (5) Post-processing
[0131] The graphitized material was depolymerized in a depolymerizer with a main frequency of 12 Hz and D was controlled. V 50 is 11.0±1.5μm, thus obtaining artificial graphite.
[0132] Example 6
[0133] This embodiment describes a process for preparing artificial graphite, which includes the following steps.
[0134] (1) Select a graphitization binder
[0135] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6% (T IFT -T SP ) / T SP =0.04. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA aqueous solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0136] (2) Mixing
[0137] A primary mixture was prepared by mixing needle coke (Dv50 9.5±1.5μm, volatile matter 5.3%), oil-based asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of oil-based asphalt added was 3.04 wt.% (compared to needle coke), resulting in a carbon residue of 1.75% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.304 wt.% and 0.051 wt.% (compared to needle coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 2.65 wt.% (compared to needle coke), the amount of PAA solution added is 0.56 wt.% (compared to needle coke), therefore the residual carbon content of component B is 1.04%, and water accounts for 8.7% of the total mass of the mixture.
[0138] (3) Molding, drying and carbonization
[0139] The mixture was extruded to form spheres with a diameter of 19.2 mm. The extruded spheres were then heat-treated at 120°C for 5 hours, followed by heating to 180°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was measured. 烘干 The Pa is 125.3 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化 The pressure is 77.8 kPa and the diameter is 18.7 mm.
[0140] (4) Continuous graphitization
[0141] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 26.7 kPa.
[0142] (5) Post-processing
[0143] The graphitized material was depolymerized in a depolymerizer with a host frequency of 17Hz and the DV50 was controlled to be 11.0±1.5μm to obtain artificial graphite.
[0144] Example 7
[0145] (1) Select a graphitization binder
[0146] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6% (T IFT -T SP ) / T SP =0.04. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA aqueous solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0147] (2) Mixing
[0148] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 18.0±1.5μm, volatile matter ≤1.0%), oil-based asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of oil-based asphalt added was 3.04 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.75% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.304 wt.% and 0.051 wt.% (compared to calcined petroleum coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 2.65 wt.% (compared to calcined petroleum coke), the amount of PAA solution added is 0.56 wt.% (compared to calcined petroleum coke), therefore the residual carbon content of component B is 1.04%, and water accounts for 18.0% of the total mass of the mixture.
[0149] (3) Molding, drying and carbonization
[0150] The mixture was extruded to form spheres with a diameter of 19.2 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 180°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was measured. 烘干 The Pa is 130.7 kPa, and then carbonized at 1150 °C for 5 h to obtain a carbide. The pulverization resistance factor η of the carbide is... 碳化 The pressure is 79.4 kPa and the diameter is 18.7 mm.
[0151] (4) Continuous graphitization
[0152] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 6 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 28.5 kPa.
[0153] (5) Post-processing
[0154] The graphitized material was depolymerized in a depolymerizer with a host frequency of 18Hz and the DV50 was controlled to be 11.0±1.5μm to obtain artificial graphite.
[0155] Example 8
[0156] This embodiment describes a process for preparing artificial graphite, which includes the following steps.
[0157] (1) Select a graphitization binder
[0158] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6% (T IFT -T SP ) / T SP =0.04. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA aqueous solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0159] (2) Mixing
[0160] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%), oil-based asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of oil-based asphalt added was 3.04 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.75% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.304 wt.% and 0.051 wt.% (compared to calcined petroleum coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 2.65 wt.% (compared to calcined petroleum coke), the amount of PAA solution added is 0.56 wt.% (compared to calcined petroleum coke), therefore the residual carbon content of component B is 1.02%, and water accounts for 8.7% of the total mass of the mixture.
[0161] (3) Molding, drying and carbonization
[0162] The mixture was extruded to form spheres with a diameter of 19.2 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 180°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was measured. 烘干 The Pa is 131.8 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化 The pressure is 81.8 kPa and the diameter is 18.6 mm.
[0163] (4) Continuous graphitization
[0164] The carbide was subjected to graphitization treatment in a continuous graphitization furnace at a temperature of 2650℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 29.8 kPa.
[0165] (5) Post-processing
[0166] The graphitized material was depolymerized in a depolymerizer with a host frequency of 19 Hz and the DV50 was controlled to be 11.0 ± 1.5 μm to obtain artificial graphite.
[0167] Example 9
[0168] This embodiment describes a process for preparing artificial graphite, which includes the following steps.
[0169] (1) Select a graphitization binder
[0170] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6% (T IFT -T SP ) / T SP = 0.04. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA aqueous solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0171] (2) Mixing
[0172] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%), oil-based asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of oil-based asphalt added was 3.04 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.75% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.304 wt.% and 0.051 wt.% (compared to calcined petroleum coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 2.65 wt.% (compared to calcined petroleum coke), the amount of PAA solution added is 0.56 wt.% (compared to calcined petroleum coke), therefore the residual carbon content of component B is 1.04%, and water accounts for 8.7% of the total mass of the mixture.
[0173] (3) Molding, drying and carbonization
[0174] The mixture was extruded to form spheres with a diameter of 19.2 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 180°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was measured. 烘干 The Pa is 132.5 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化 The pressure is 83.7 kPa and the diameter is 18.8 mm.
[0175] (4) Continuous graphitization
[0176] The carbide was subjected to graphitization treatment in a continuous graphitization furnace at a temperature of 2850℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 33.5 kPa.
[0177] (5) Post-processing
[0178] The graphitized material was depolymerized in a depolymerizer with a host frequency of 21 Hz and the DV50 was controlled to be 11.0 ± 1.5 μm to obtain artificial graphite.
[0179] Comparative Example 1
[0180] This comparative example illustrates a process for preparing artificial graphite, which includes the following steps.
[0181] Calcined petroleum coke (Dv50 of 11.5±1.5μm and volatile matter ≤1.5%) was loaded into a graphite crucible and graphitized in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain artificial graphite.
[0182] Comparative Example 2
[0183] This comparative example illustrates a process for preparing artificial graphite, which includes the following steps.
[0184] (1) Select a graphitization binder
[0185] The adhesive consists of component A and component B. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6%. IFT -T SP ) / T SP =0.04. Component B contains thermosetting phenolic resin and PAA solution. The coking value of the thermosetting phenolic resin is 37.7%, and the solid content of the PAA aqueous solution is 40%, the molecular weight is 400,000, and the coking value is 7.2%.
[0186] (2) Mixing
[0187] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%) with oil-based asphalt using vitamin C (VC). The amount of oil-based asphalt added was 3.04 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.75% for component A. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The kneader operated at 35 Hz for 2 hours. The amount of thermosetting phenolic resin added was 2.65 wt.% (compared to calcined petroleum coke), and the amount of PAA solution added was 0.56 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.02% for component B. Water accounted for 8.7% of the total mass of the mixture.
[0188] (3) Molding, drying and carbonization
[0189] The mixture was extruded to form spheres with a diameter of 19.2 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 180°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was measured. 烘干 The Pa is 118.4 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The pulverization resistance factor η of the carbide is... 碳化 The pressure is 65.4 kPa and the diameter is 18.7 mm.
[0190] (4) Continuous graphitization
[0191] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 24.8 kPa.
[0192] (5) Post-processing
[0193] The graphitized material was depolymerized in a depolymerizer with a host frequency of 22Hz and the DV50 was controlled to be 11.0±1.5μm to obtain artificial graphite.
[0194] Comparative Example 3
[0195] This comparative example illustrates a process for preparing artificial graphite, which includes the following steps.
[0196] (1) Select a graphitization binder
[0197] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 72.5% (T IFT -T SP ) / T SP =0.20. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA aqueous solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0198] (2) Mixing
[0199] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%), oil-based asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of oil-based asphalt added was 2.41 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.75% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.289% and 0.058% (compared to calcined petroleum coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 2.65 wt.% (compared to calcined petroleum coke), the amount of PAA solution added is 0.56 wt.% (compared to calcined petroleum coke), therefore the residual carbon content of component B is 1.02%, and water accounts for 8.7% of the total mass of the mixture.
[0200] (3) Molding, drying and carbonization
[0201] The mixture was extruded to form spheres with a diameter of 19.2 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 180°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was measured. 烘干 The Pa is 134.2 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The pulverization resistance factor η of the carbide is... 碳化 The pressure is 76.7 kPa and the diameter is 18.7 mm.
[0202] (4) Continuous graphitization
[0203] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 27.1 kPa.
[0204] (5) Post-processing
[0205] The graphitized material was depolymerized in a depolymerizer with a host frequency of 22Hz and the DV50 was controlled to be 11.0±1.5μm to obtain artificial graphite.
[0206] Comparative Example 4
[0207] This comparative example illustrates a process for preparing artificial graphite, which includes the following steps.
[0208] (1) Select a graphitization binder
[0209] The adhesive consists of components A, B, and C. Component A is T. SP Modified asphalt at temperatures below 150℃ has a coking value of 55.3% (T IFT -T SP ) / T SP = 0.65. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0210] (2) Mixing
[0211] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%), modified asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of modified asphalt added was 3.16 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 1.75% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.288 wt.% and 0.048 wt.% (compared to calcined petroleum coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 2.65 wt.% (compared to calcined petroleum coke), the amount of PAA solution added is 0.56 wt.% (compared to calcined petroleum coke), therefore the residual carbon content of component B is 1.02%, and water accounts for 9.3% of the total mass of the mixture.
[0212] (3) Molding, drying and carbonization
[0213] The mixture was extruded to form spheres with a diameter of 20.8 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 170°C and holding for 4 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was determined. 烘干 The Pa is 126.5 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化 The pressure is 75.4 kPa and the diameter is 20.3 mm.
[0214] (4) Continuous graphitization
[0215] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 26.2 kPa.
[0216] (5) Post-processing
[0217] The graphitized material was depolymerized in a depolymerizer with a host frequency of 17Hz and the DV50 was controlled to be 11.0±1.5μm to obtain artificial graphite.
[0218] Comparative Example 5
[0219] This comparative example illustrates a process for preparing artificial graphite, which includes the following steps.
[0220] (1) Select a graphitization binder
[0221] The adhesive consists of components A, B, and C. Component A is T. SP Oil-based asphalt at temperatures above 150℃ has a coking value of 57.6% (T IFT -T SP ) / T SP =0.04. Component B contains thermosetting phenolic resin and PAA solution. The thermosetting phenolic resin has a coking value of 37.7%, and the PAA solution has a solid content of 40%, a molecular weight of 400,000, and a coking value of 7.2%. Component C includes terephthalic acid and p-toluenesulfonic acid.
[0222] (2) Mixing
[0223] A primary mixture was prepared by mixing calcined petroleum coke (Dv50 11.5±1.5μm, volatile matter ≤1.5%), oil-based asphalt, terephthalic acid, and p-toluenesulfonic acid with vitamin C. The amount of oil-based asphalt added was 4.34 wt.% (compared to calcined petroleum coke), resulting in a carbon residue of 2.50% for component A. The amounts of terephthalic acid and p-toluenesulfonic acid introduced were 0.304 wt.% and 0.051 wt.% (compared to calcined petroleum coke), respectively. The primary mixture, thermosetting phenolic resin, PAA solution, and water were then added to a kneader and kneaded to obtain a final mixture. The mixing machine operates at a speed of 35 Hz, the mixing time is 2 hours, the amount of thermosetting phenolic resin added is 5.30 wt.% (compared to calcined petroleum coke), the amount of PAA solution added is 0.694 wt.% (compared to calcined petroleum coke), therefore the residual carbon content of component B is 2.02%, and water accounts for 8.7% of the total mass of the mixture.
[0224] (3) Molding, drying and carbonization
[0225] The mixture was extruded to form spheres with a diameter of 19.2 mm. The extruded spheres were then heat-treated at 85°C for 8 hours, followed by heating to 180°C and holding for 3 hours to obtain dried spheres. The powdering resistance factor η of the dried spheres was measured. 烘干 The Pa is 148.5 kPa, and then carbonized at 1150 °C for 6 h to obtain a carbide. The powdering resistance factor η of the carbide is... 碳化 The pressure is 93.2 kPa and the diameter is 18.7 mm.
[0226] (4) Continuous graphitization
[0227] The carbide was subjected to graphitization in a continuous graphitization furnace at a temperature of 2750℃ for 4 hours to obtain a graphitized body. The graphitization resistance factor η of the graphitized body was [not specified]. 石墨化 The value is 63.7 kPa.
[0228] (5) Post-processing
[0229] The graphitized material was depolymerized in a depolymerizer with a host frequency of 28Hz and the DV50 was controlled to be 11.0±1.5μm to obtain artificial graphite.
[0230] The artificial graphite prepared in Examples 1 to 9 and Comparative Examples 1 to 5 was subjected to physical and electrochemical performance tests under the following conditions, and the test results are shown in Table 1.
[0231] (1) Physical properties
[0232] The specific surface area was obtained by measuring the specific surface area using a specific surface area meter.
[0233] The tap density (tap) was obtained by testing with a tap density meter.
[0234] The degree of graphitization is calculated from the interlayer spacing d002 using Franklin's formula.
[0235] (2) Quantitative capacity performance test
[0236] The artificial graphite prepared in Examples 1 to 9 and Comparative Examples 1 to 5 were used as active materials, mixed with an aqueous dispersion of acrylonitrile copolymer binder (LA132, solid content 15%) and conductive agent (Super-P) at a mass ratio of 92:6:2. A certain amount of water was added as a solvent, and the mixture was homogenized to adjust the solid content of the slurry to 55%. The slurry was then coated onto copper foil and vacuum dried and rolled to prepare a negative electrode sheet. The counter electrode was a lithium metal sheet, the electrolyte was a 1 mol / L LiPF6 solution (the solvent was a mixture of EC, DMC, and EMC in a volume ratio of 1:1:1), and the separator was a polypropylene microporous membrane. The cells were assembled into coin cells in a glove box filled with inert gas. Charge-discharge tests of the coin cells were conducted on the LANHE battery testing system of LANHE Electronics Co., Ltd. Under normal temperature conditions, the voltage is discharged to 0.01V with a constant current of 0.1C, then discharged to 0.005V with a constant current of 0.02C, and then charged to 1.5V with a constant current of 0.1C, thus obtaining the first reversible capacity (first efficiency) and the first coulombic efficiency.
[0237] Table 1 shows the performance test results of the artificial graphite prepared in Examples 1 to 9 and Comparative Examples 1 to 5.
[0238]
[0239] As shown in Table 1, Examples 1-9 show that continuous graphitization using composite binders containing soft carbon binders, hard carbon binders, and crosslinking agents with certain parameters and contents can yield high-performance artificial graphite, especially with a significant improvement in the first coulombic efficiency.
[0240] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A composite binder for producing artificial graphite from graphite precursors through continuous graphitization, characterized in that, The product comprises three components: A, B, and C. Component A includes a soft carbon binder, component B includes a hard carbon binder, and component C includes a crosslinking agent. The soft carbon binder satisfies either equation one or equation two. The residual carbon content of component A is 'a', the residual carbon content of component B is 'b', a+b≤2.90%, a / (a+b)≥60%, and the mass ratio of component C to component A is ≤20%. SP T is the temperature at which the soft carbon binder transitions from a solid to a molten liquid state. IFT The temperature at which the contact angle between the soft carbon binder and the base coke raw material is 90° is defined. The residual carbon content is the product of the coking value and its mass percentage in the graphite precursor. The hard carbon binder provides structural support at medium to low temperatures between 200 and 400°C. When T SP At ≤ 150℃, (T IFT -T SP ) / T SP ≤ 0.30 Relationship 1 When T SP When the temperature is >150℃, (T IFT -T SP ) / T SP Relationship 2 ≤ 0.12 2. The composite adhesive according to claim 1, characterized in that, Includes at least one of the following features ① to ⑥: ①The soft carbon binder is selected from at least one of oil-based asphalt, coal-based asphalt, impregnated asphalt, modified asphalt, and high softening point asphalt; ②The hard carbon-based binder is selected from at least one of phenolic resin and epoxy resin; ③ The crosslinking agent is selected from at least one of terephthalic acid, benzaldehyde, p-methylbenzaldehyde, p-phenylenediamine, p-toluenesulfonic acid, sulfur, N-bromosuccinimide and N-iodosuccinimide; ④ The B component further includes a polymer adhesive, which is selected from at least one of polyacrylic acid, styrene-butadiene-styrene block copolymer, ethylene-octene copolymer, ethylene-ethyl acrylate copolymer, styrene-ethylene / butene-styrene triblock copolymer, ethylene-octene copolymer, chloroprene rubber, ethylene-ethyl acrylate copolymer, sodium carboxymethyl cellulose, polyvinylidene fluoride, and polyethylene terephthalate; ⑤ The T SP Results obtained using Mettler DP70 testing; ⑥ The T IFT The results were obtained using a Dataphysics OCA20 measuring instrument.
3. A process for preparing artificial graphite, characterized in that, Including the following steps: (1) Select a graphitization binder The adhesive is the composite adhesive as described in claim 1 or 2; (2) Mixing The graphite precursor, component A, component B, component C, and solvent are mixed to obtain a mixture; (3) Molding, drying and carbonization The mixture is sequentially pressed into balls, dried, and carbonized to obtain a carbonized body, the pulverization resistance factor of which is η. 碳化 50kPa≤η 碳化 ≤90kPa; (4) Continuous graphitization The carbide is graphitized to obtain a graphitized body, and the graphitized body has a powdering resistance factor of η. 石墨化 20kPa≤η 石墨化 ≤36kPa; (5) Post-processing The graphitized body is then post-processed.
4. The preparation process of artificial graphite according to claim 3, characterized in that, Includes at least one of the following features (1) to (12): (1) The graphite precursor is selected from at least one of needle coke, calcined needle coke, petroleum coke, calcined petroleum coke and isotropic coke; (2) The particle size Dv50 of the graphite precursor is 6~25μm; (3) The solvent is selected from at least one of water, ethanol, isopropanol, toluene, tetrahydrofuran, N-methyl-2-pyrrolidone, n-heptane, n-hexane, cyclohexane, acetone and N,N-dimethylformamide; (4) The solvent accounts for 7-25% of the mass of the mixture; (5) The carbide is a sphere, an ellipsoid, or a cylinder; (6) The carbide is a cylinder with a diameter of 8~40mm and a height h of 8~30mm; (7) The powdering resistance factor after drying is η 烘干 120kPa≤η 烘干 ≤145kPa; (8) The equipment used for mixing is selected from glass reactors, stainless steel reactors, double planetary mixers, kneaders, VC mixers, fusion machines or three-dimensional mixers; (9) The pressing method is selected from molding, roller extrusion, rotary rolling or extrusion molding; (10) The drying temperature is 70~350℃ and the time is 2~15h; (11) The carbonization temperature is 900~1250℃ and the time is 3~15h; (12) The post-processing includes depolymerization, which is performed using a depolymerization machine with a host frequency of 10~25Hz.
5. The preparation process of artificial graphite according to claim 3, characterized in that, The graphitization process is carried out in a continuous graphitization furnace.
6. The preparation process of artificial graphite according to claim 5, characterized in that, The temperature of the continuous graphitization furnace is 2600~3200℃, and the time is 2~10h.
7. The artificial graphite prepared by the artificial graphite preparation process according to any one of claims 3 to 6, characterized in that, It has at least one of the following characteristics (a) to (b): (i) The particle size Dv50 of the artificial graphite is 7~25μm; (ii) The specific surface area of the artificial graphite is 0.5~2.5m². 2 / g; (iii) The specific capacity of the artificial graphite is 320~355mAh / g; (iv) The initial coulombic efficiency of the artificial graphite is ≥92.5%.
8. The artificial graphite prepared by the preparation process of artificial graphite according to any one of claims 3 to 6, or the application of the artificial graphite according to claim 7 in a battery.
9. A secondary battery, comprising a positive electrode material, a negative electrode material, and an electrolyte, characterized in that, The negative electrode material includes artificial graphite prepared by the artificial graphite preparation process according to any one of claims 3 to 6 or the artificial graphite according to claim 7.
Citation Information
Patent Citations
Negative active material, composite negative pole piece and quick-charge lithium ion battery
CN111613783A
Hard carbon and soft carbon co-modified artificial graphite negative electrode material and preparation method thereof
CN114852991A